Audit procedure of verification of alternative cash assistance of ACNABIN chartered accountants - Nayon, Md Rakibul Hassan (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.